Arbuscular mycorrhizal fungi strongly influence the endorhizosphere of grapevine rootstock with soil type as a key factor - Štůsková, K; Vavřiník, A; Hakalová, E; Čechová, J; Gramaje, D; Eichmeier, A (Mycorrhiza, 2025)
Arbuscular mycorrhizal fungi (AMF) play a crucial role in enhancing the health and productivity of host plants, including grapevine. By forming symbiotic relationships with plant roots, AMF significantly improve water uptake and nutrient absorption, particularly phosphorus (P) and nitrogen (N). This study evaluated the microbiome composition and AMF colonization in the grapevine endorhizosphere across five wine-growing sub-regions in the Czech Republic. In all five sub-regions, in terms of composition of the fungal microbiome, the phyla Ascomycetes and Basidiomycetes were most numerous. Additionally, the study confirmed that LSU primers are more sensitive than ITS primers for AMF sequencing. While the representation of the phylum Glomeromycetes ranged from 0.07% to 5.65% in the ITS library, it was significantly higher, ranging from 83.74% to 98.71%, in the LSU library. The most significant difference compared to other sub-regions was observed in the Slovácko sub-region, where the soil had a low pH, a different texture (sandy loam), reduced micronutrient concentration, and low organic matter. The application of chemical plant protection products to grapevines also could have played a significant role, with 49 applications recorded in the Slovácko sub-region during the three years preceding sample collection. In other sub-regions, chemical treatments were conducted only 19-26 times. These factors resulted in only trace amounts of AMF being detected in Slovácko. Furthermore, it was demonstrated that AMF positively influenced the phosphorus concentration in the soil and reduced the presence of certain fungal pathogens.
Keywords: Symbiosis; Soil Microbiology; Grapevine; rhizosféra; Česká republika; Plant Roots; Czech Republic; Microbiome; Arbuscular mycorrhizal fungi; Microbiota; půda; mikrobiota; kořeny rostlin; Vitis; Mycorrhizae; Endorhizosphere; mykorhiza; půdní mikrobiologie; symbióza; Rhizosphere; Metagenomics; Soil characteristics; fosfor; Phosphorus; Soil